A Comparative study on Vamana Karma by Using Shuddha Ghrita and Samskarita Ghrita as Abhyantara Snehapana in Ekakushtha w s r to Psoriasis - Hemang Ragvani, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
A Comparative study on Vamana Karma by Using Shuddha Ghrita and Samskarita Ghrita as Abhyantara Snehapana in Ekakushtha w s r to Psoriasis